2019
DOI: 10.1186/s12964-019-0446-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PKCι-PAK1 signaling pathways in EGFR and KRAS mutant adenocarcinoma and lung squamous cell carcinoma

Abstract: Introductionp21-activated kinase 1 (PAK1) stimulates growth and metastasis in non-small cell lung cancer (NSCLC). Protein kinase C iota (PKCι) is an enzyme highly expressed in NSCLC, regulating PAK1 signaling. In the present study we explored whether the PKCι-PAK1 signaling pathway approach can be an efficient target in different types of NSCLC cell and mouse models.MethodsThe effect of IPA-3 (PAK1 inhibitor) plus auranofin (PKCι inhibitor) combination was evaluated by cell viability assay, colony formation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…7,8 KRAS mutations correlate significantly to poor therapeutic response in NSCLC patients. [9][10][11] Therefore, it is essential to develop novel KRAS-targeting drugs for treating recalcitrant NSCLC patients with KRAS mutations.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 KRAS mutations correlate significantly to poor therapeutic response in NSCLC patients. [9][10][11] Therefore, it is essential to develop novel KRAS-targeting drugs for treating recalcitrant NSCLC patients with KRAS mutations.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients treated with EGFR tyrosine kinase inhibitors usually acquire resistance after 9-12 months. Previous studies on EGFR mutations showed that a PAK1 inhibitor, administered in combination with a selective inhibitor of protein kinase C, was effective against the acquisition of resistance induced by EGFR tyrosine kinase inhibitors [28,29]. We found that the five-year mortality rates were lower in patients with PAK1-negative than in PAK1-positive EGFR mutant lung cancer.…”
Section: Discussionmentioning
confidence: 56%
“…Since it has been proven that OTSSP167 does not selectively inhibit MELK [49,50], we cannot exclude that part of the anti-growth function (s) of OTSSP167 is due to off-target effects of the drug. In support of the latter hypothesis, a recent investigation showed that OTSSP167 hampers the proliferation and colony formation ability of lung cancer cell lines, as well as carcinogenesis in lung cancer xenografts via the suppression of the PAK1 protooncogene [52]. Furthermore, it has been found that MELK suppression by siRNA did not recapitulate the mitotic effects of OTSSP167 treatment in MCF7 and Hela cancer cell lines.…”
Section: Discussionmentioning
confidence: 97%